Answer:
A. [tex] y_1 = -m(x_2 - x_1) + y_2 [/tex]
Step-by-step explanation:
Given, slope formula = [tex] m = \frac{y_2 - y_1}{x_2 - x_1} [/tex]
To find an equivalent equation, let's make [tex] y_1 [/tex] the subject of the formula.
[tex] m = \frac{y_2 - y_1}{x_2 - x_1} [/tex]
Cross multiply
[tex] 1(y_2 - y_1) = m(x_2 -x_1) [/tex]
[tex] y_2 - y_1 = m(x_2 - x_1) [/tex]
Subtract [tex] y_2 [/tex] from both sides
[tex] y_2 - y_1 - y_2 = m(x_2 -x_1) - y_2 [/tex]
[tex] - y_1 = m(x_2 - x_1) - y_2 [/tex]
Divide both sides by -1
[tex] \frac{- y_1}{-1} = \frac{m(x_2 -x_1) - y_2}{-1} [/tex]
[tex] y_1 = -m(x_2 - x_1) + y_2 [/tex]